Design and Verification of Sector Vortex Archimedean Spiral Phased Array Transducer for Improving Focus Acoustic Pressure - LU, Xiaodan; ZENG, Deping (Archives of Acoustics, 2024)
The emergence of high-intensity focused ultrasound applications brings great potential to establish noninvasive therapeutic treatment in place of conventional surgery. However, the development of ultrasonic technology also poses challenges to the design and manufacture of high-power ultrasound transducers with sufficient acoustic pressure. Here, the design of a sector vortex Archimedean spiral phased array transducer that is able to enhance focal acoustic pressure is proposed by maximizing the filling factor of the piezoelectric array. The transducer design was experimentally verified by hydrophone measurements and matched well with acoustic simulation studies. The focal deflection was shown to be feasible up to ±9 mm laterally and up to ±20 mm axially, where the effective focal acoustic pressure can be maintained above 50% and the level of the grating lobe below 30%. Furthermore, a homogeneous pressure distribution without secondary focus was observed in the pre-focal region of the transducer. The rational design of a high-intensity focused ultrasound transducer indicates promising development in the treatment of deep tissue thermal ablation for clinical applications.